2020
DOI: 10.1002/hep.31068
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Sequencing Identifies CircASAP1 as a Key Regulator in Hepatocellular Carcinoma Metastasis

Abstract: Background and Aims There is growing evidence that single‐stranded, circular RNA (circRNA) plays a key role in the development of certain cancers, including hepatocellular carcinoma (HCC). It is less clear, however, what role circRNA plays in HCC metastasis. Approach and Results In this study, through circRNA sequencing, we identified a circRNA: circASAP1 (a circRNA derived from exons 2 and 3 of the ASAP1 gene, hsa_circ_0085616), which is associated with pulmonary metastasis after curative resection in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
171
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(183 citation statements)
references
References 41 publications
3
171
0
Order By: Relevance
“…CircRNAs have also shown potential effect to in uence the tumor microenvironment, Circular RNA CDR1as may play a speci c role in immune and stromal cell in ltration in tumor tissue, especially those of CD8 + T cells, activated NK cells, M2 macrophages [31]. Circular RNA CircASAP1 could mediates tumor-associated-macrophage in ltration by regulating the miR-326/miR-532-5p-CSF-1 pathway [9]. So, targeting circular RNA on the tumor microenvironment may be a potential direction in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircRNAs have also shown potential effect to in uence the tumor microenvironment, Circular RNA CDR1as may play a speci c role in immune and stromal cell in ltration in tumor tissue, especially those of CD8 + T cells, activated NK cells, M2 macrophages [31]. Circular RNA CircASAP1 could mediates tumor-associated-macrophage in ltration by regulating the miR-326/miR-532-5p-CSF-1 pathway [9]. So, targeting circular RNA on the tumor microenvironment may be a potential direction in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CircBACH1 (hsa_circ_0061395) is signi cantly upregulated in HCC tissue andcircBACH1 knockdown suppresses the proliferation and increased apoptosis of HCC cells by regulating p27 repression via HuR [8]. CircASAP1 acts as a ceRNA for miR-326 and miR-532-5p to mediates tumor-associated-macrophage (TAM) in ltration [9]. As a consequence, emerging evidences support the critical roles of circRNA for HCC tumorigenesis and development.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNA CircASAP1 could mediates tumor-associated-macrophage in ltration by regulating the miR-326/miR-532-5p-CSF-1 pathway [14]. So, targeting circular RNA on the tumor microenvironment may be a potential direction in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CircBACH1 (hsa_circ_0061395) is signi cantly upregulated in HCC tissue and circBACH1 knockdown suppresses the proliferation and increased apoptosis of HCC cells by regulating p27 repression via HuR [13]. CircASAP1 acts as a ceRNA for miR-326 and miR-532-5p to mediates tumor-associated-macrophage (TAM) in ltration [14]. As a consequence, emerging evidences support the critical roles of circRNA for HCC tumorigenesis and development.…”
Section: Introductionmentioning
confidence: 99%
“…These RNAs perform a variety of biological functions, such as regulating genes. In recent years, a growing number of studies have shown that circRNAs are inextricably linked to the malignant process of many cancers [12][13][14][15][16]. Some researchers con rmed that circRNAs could promote CC [17][18][19], while some suggested that multiple circRNAs were associated with the pathological process of CC [20][21][22].…”
mentioning
confidence: 99%